Studying the impact of intermittent variations using sensitivity analysis - Khan, S.; Phillips, P.; Jennions, Ian K. (British Institute of Non-destructive Testing, 2015)
Fault diagnostics focuses on the detection, identification and isolation of failures. However, this becomes challenging when investigating fault alarms that cannot be verified, diagnosed or even duplicated under standard manual inspection regimes. To improve system effectiveness, it is essential to investigate these instances, along with the effects of design parameters on system dynamic characteristics. Recent research has identified intermittent fault behaviour within components as one of the primary focuses for false alarms, and hence a direct consequence to the phenomenon of 'no fault found'. This paper examines the performance characteristics of an electronic system under intermittent component variations. Understanding occurrences in parameter deviations (and their impact) can help with understanding the requirements for improving system fault tolerance. It is shown that, in many cases of practical importance, components do not have the same sensitivity to intermittent variations and hence can be better suited for monitoring. The analysis provides extra information and guidance for the maintenance decision-making process in organisations on resource requirements.
Keywords: Sensitivity analysis; No fault found; Fourier series; Mathematical modelling; Model-based fault detection